Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
[tex]Distance\ Formula \\ \sqrt{(y2-y1)^{2}+(x2-x1)^{2}} \\ \\ \sqrt{(-2-(-8))^{2}+(-6-0)^{2}} \\ \\ \sqrt{(6)^{2}+(-6)^{2}} \\ \\ \sqrt{36+36}= \sqrt{72} \\ \\ \sqrt{9*8}= 3\sqrt{8}=3 \sqrt{4*2}=6 \sqrt{2} \\ \\ \boxed{6 \sqrt{2} } [/tex]
You can use the distance formula for this. √(x-x)² + (y-y)²
So, √(0 + 6) + (-8 +2)
=√(6)² + (-6)²
=√36 + 36
=√72
=6√2
So, the distance between those points is 6√2 units.
So, √(0 + 6) + (-8 +2)
=√(6)² + (-6)²
=√36 + 36
=√72
=6√2
So, the distance between those points is 6√2 units.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.